Life Style-Related Osteoporosis Preventive Behaviors among Nursing and Midwifery Students - E Ahmadnia; E Shakibazadeh; T Emamgholi Khooshehcheen (Tehran University of Medical Sciences, 2010)
Background & Objective: Life style has potential role in bone mass density and prevention of osteoporosis in adolescents. The aim of this study was to determine the life style of female students influencing osteoporosis prevention in Nursing and Midwifery school at Zanjan University of Medical Sciences.Methods & Materials: All female students (n=166) were recruited in this cross-sectional study. Data were gathered using three questionnaires: 1) demographic questionnaire, 2) General Practitioner Physical Activity Questionnaire, and 3) dietary recall questionnaire. Validity and reliability of the questionnaires were determined. Date was analyzed using descriptive statistic, Chi-square, and t-test.Results: Mean calcium intake was statistically different between dormitory and non-dormitory students (P<0.001). Regarding physical activity, only 19.2% of the students had appropriate activity. The main activity of the students was walking (83.5%). There was a significant difference between economic status and life style (P=0.047). There was no statistically significant difference between life style with the parents;apos educational level, and the educational program.Conclusion: It seems that life style-related osteoporosis preventive behaviors are not appropriate among nursing and midwifery students. Planning appropriate educational programs could promote high standard nutritional plans and physical activity among the female students.